Penser l’accompagnement éducatif cinéphile dans un environnement numérique - Christel Taillibert (Communiquer)
This article proposes a reflection on the way in which cinephile educational support, as they originally manifest in classroom sessions, find variations within the framework of cinephiles Video on Demand. Based on the analysis of a corpus of platforms and a series of interviews with their creators and facilitators, this article describes and analyzes the possibilities of an online transposition of the principles of vertical education, which mainly take the form of online informational underpinning, and horizontal education principles. The slightest attention paid to this second point will lead us to reflect on the role carried out by these actors regarding the whole cinephile system. The will to preserve, in the global cinephile system, the place occupied by traditional face-to-face devices (the film theater, the festival, the film library, etc.) probably explains the reluctance in inventing digital spaces of sociability linked to these new online places for the films’ discovery.